Treatment of migraine with fremanezumab and sleep: A preliminary case series - Agustin Melo-Carrillo; Joaquin Gorrissen; Amanda Macone; Rami Burstein; Sait Ashina (Cephalalgia Reports)
Background Migraine is a prevalent neurological disease that has socioeconomic and functional impact. It is also frequently associated with sleep disorders. The intricate relationship between migraine and sleep disturbances involves complex neurobiological circuits within the brain, including those that govern the sleep-wake transition. Observational evidence suggests that sleep disruption may trigger migraine episodes and contribute to their progression from episodic to chronic state. Our study aimed to explore the impact of fremanezumab, a calcitonin gene-related peptide (CGRP) monoclonal antibody (mAb), on sleep in patients with migraine. Methods Employing a prospective, observational, open-label treatment approach, this preliminary case series assessed sleep quality using daily e-diaries and the Insomnia Severity Index over four months: one month pre-treatment and three months during treatment with fremanezumab. Results Analyzing data from six cases, we found associations between improvements in migraine and sleep quality in five cases and no association in one case in which improvement in sleep was recorded, despite a lack of improvement in migraine frequency and intensity. Conclusion This study suggests that the primary mechanism by which fremanezumab improves sleep involves a reduction in headache frequency and severity. The possibility that fremanezumab acts directly on sleep-promoting neurons in the hypothalamus is also discussed. These findings emphasize the need for further research to elucidate the precise mechanisms by which CGRP mAbs influence sleep pathology. Trial registration NCT04693533.